Huling bati - Poblete, Alexandra Maria De Leon 1993- (2013)
"There is a growing individualism among people in the present time that individuals tend to act according to what they think will benefit them. Huling Bati is a film that shows that every individual can have an effect, whether consciously or unconsciously, whether for better or for worse, on other people. We have that capability. Set in a public school, the film follows an old "terror" teacher about to retire from teaching and go aboard to live with her younger sibling. On her last day in school, she takes it as an ordinary day but unexpectedly somehow felt emptiness as she remains distant with everyone around her. On this last day as well, one of her problem student, who was in risk of not graduating, suddenly changes, to her and his classmates surprise which leads to the teacher's realization on things she did not take notice of before."